Iodination of Alkylbenzenes using Benzyltriphenylphosphonium Dichromate / I2 System - R. Sathiyapriya; R. Joel Karunakaran (E-Journal of Chemistry)
An efficient and rapid method have been found using benzyltriphenylphosphonium dichromate (PhCH2PPh3)2Cr2O7 as an oxidant along with molecular iodine for the iodination of aromatic compounds. Iodination of a wide variety of alkyl benzenes were done under dichloromethane solvent system and high yields of iodo products were obtained